علاقة استخدام التعبير العامي في اللغة إندونيسيا بأخلاق طلاب قسم تعليم اللغة العربية بجامعة مادورا الإسلامية الحكومية - Nurdiana Arifah; Abd Rahman Romadhon; Haruna Abubakar Haruna (Journal of Arabic Language Teaching, 2023)
This article aims to determine the correlation between the use of colloquial in Indonesian and the morals of Arabic language education students IAIN Madura. This study used a quantitative research approach with a correlational method. Data was collected through questionnaires with a sample of 25% of the total population, namely 33 people. The results showed that PBA IAIN Madura students often use colloquial in Indonesian, especially to their friends, and the morals of PBA IAIN Madura students are excellent, which is shown by a score of 88.26%. The results of the analysis obtained also stated that rXY = -0.464 with N of 33 and a significance level of 5%, then r-table = 0.344. From this data, it can be concluded that recalculate < r-table. So, there is no significant correlation between the use of colloquials in Indonesian and the morals of PBA IAIN Madura students.